Impact of Current Limitation of Grid-forming Voltage Source Converters on Power System Stability. Issue 2 (2020) - Schöll, Christian; Lens, Hendrik
Abstract: Grid-forming voltage source converters (VSC) have important characteristics of synchronous generators (SG). These include the provision of inertia and, in particular, voltage source behavior. These properties are required to make interconnected power systems with up to 100 % converter based generation possible. However, grid-forming VSC can not replace an important feature of SG: overcurrent capability. This property of SG contributes to power system stability. In the case of severe disturbances, SG may initially be overloaded before the load is gradually shared with other feed-ins. Due to the risk of damage, VSC have an overcurrent protection. However, most grid-forming VSC control concepts do not incorporate a sophisticated overcurrent limitation. This paper shows, by means of simulations, that current limiting of grid-forming VSC can lead to significant power system stability issues due to unsuccessful load sharing between other feed-ins. In addition, the paper shows, that with an increasing share of constant power loads, these issues can occur sooner.